(untitled) (Tempo e Argumento, 2020)
During the preparations for the Football World Cup in Brazil, Florianópolis received, in February 2014, a delegation of coaches of the national teams classified for the tournament, as well as journalists from all over the world. Sectors linked to tourism and the press gave special highlights to the event, hoping to invigorate international tourism and show the welcoming potential of the state of Santa Catarina. On the first day of the event, the newspaper Diário Catarinense distributed a special supplement, a kind of tourist guide to the city, entitled “Welcome to Floripa;” its cover featured an advertisement for a nightclub, the Bokarra Club, bearing images of women in erotic poses, an explicit apologia for sex tourism. I analyze the media impacts of these images, offered as objects of desire; letters exchanged between a public agency and this press medium; the resonance of this publication for male and female readers regarding sex tourism. I observe the uses of female images in the media, from the perspective of gender relations.